O discurso sobre a cosmologia contemporânea e o seu ensino nas diferentes falas da academia - Martins, Milene Rodrigues (2016)
The research focused on the teaching of Cosmology is still walking in slow steps, since there are few studies conducted with this focus. From this perspective, considering relevant questions on the origin of the universe, this paper aims to investigate the discourse of six professors and researchers from both institutions of higher education with national and international scope. The consideration and discussion of the cosmological theories and conceptual conflicts inherent in them are necessary in the different educational levels, in order to highlight the provisional nature of scientific knowledge. Therefore, this work will be focused on three complex empirical evidences that do not allow a single interpretation: redshifts, cosmic microwave background radiation (CMB), and Quasars. The data was obtained through interviews shot for later transcription and interpretation. The data analysis was based on theoretical and methodological assumptions of phenomenological research, according to BICUDO (2000) and MARTINS (1994). Upon the end of the analysis, it is concluded that the importance of Cosmology teaching does not present any agreement among teachers and researchers, as well as the methodology to be adopted. Compared with the approach of alternative cosmological models to the standard model, the research subjects are also not in concordance. Moreover, it seems to be unanimity among the research subjects the view that in relation to the universe there is much more to be discovered, investigated and studied, since it is known only a tiny portion of the universe. Regarding the three empirical evidences (redshifts, quasars and the cosmic microwave background), the subjects who studied and discussed these topics represented only the interpretations which support the big bang theory.